The coherence between Javanese Gamelan (Traditional Instrument) and Classical Javanese Dance - Rumiwiharsih (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Gamelan as the traditional instrument of the Javanese people has an important function in the existence of Javanese dance, especially classical dance. It is called classical because it was born and developed within the Kingdom, while those born outside the Kraton (Javanese court), are called Folk Dance. Gamelan consists of two devices (laras), namely 1) slendro and 2) pelog. Both have their own characteristics. For example, from the number of blades, also the sound products. Javanese people have cultural results of art creations that are commonly referred to as adi luhung, including gamelan, and dance. The coherence between gamelan and dance is very strong, to the level of naming the dance, following the name of the gêndhing in its Karawitan. Karawitan is a combination of beating gamelan with gêndhing, or melody, or even up to the notation. Examples of strong coherence in Javanese Classical Dance, such as: 1) Srimpi Anglirmêndhung Dance, the accompaniment is Gêndhing Srimpi Anglirmêndung, Kêthuk Kalih Kêrep, Minggah Kêtawang Gêndhing Kêmenak, Suwuk, Buka Sri Narendra, Dhawah Kêtawang Langên-gita, Pelog Pathêt Barang, 2) Bêdhaya Endhol-Endhol Dance by Endhol-endhol gêndhing, 3) Golek Asmaradana Dance by Asmaradana gêndhing.